IMPLEMENTATION OF THE TEAM GAME TOURNAMENT (TGT) MODEL IN IMPROVING COLLABORATION CAPABILITY CLASS V PRIMARY SCHOOL STUDENTS - Jati Kesuma, Puthot Bagus; Rigianti, Henry Aditia (Jurnal Dikdas Bantara, 2024)
This research aims to describe the TGT model in improving collaboration skills in students. This research is descriptive research with a quantitative approach. The research was conducted on class V students at SD N 1 Sribitan, totaling 24 students, using data collection techniques through observation and tests. The data obtained was tested for validity and reliability. The results of data processing show that the collaboration abilities of class V students at SD N 1 Sribitan are categorized as always increasing in each cycle. This statement is based on the results of students' collaboration abilities, namely before the treatment the average was 60 and after the treatment in cycle I it became 72, and the results from cycle II got an average score of 90, and there was an increase in collaboration which was marked by the achievement of collaboration indicators.So it can be concluded that the application of the TGT model can have a good effect on students' collaboration abilities, because there is an increase in collaboration abilities in cycles I and II.